The Influence of Virtual Reality Content in Social Studies Learning on Critical Thinking Skills and Learning Happiness at SMP N 3 Pagedongan Banjarnegara - Asri Ratna Sari; Sriyanto Sriyanto (Universitas Muhammadiyah Enrekang, 2023)
The essence of social studies learning is to help students to develop the ability to make decisions, in a different society and the culture of an interdependent world democratic society. Thus, IPS follows an integrated perspective aimed at developing the ability to make decisions, based on the diverse public interests in social life. Social studies learning is not only limited to achieving degrees of knowledge and understanding, but is expected to be able to achieve higher degrees, namely increasing the profile of critical thinking. One of the important challenges for Social Sciences teachers is how to manage learning that is able to bring joy to learning. The research used the experimental method in the form of a true experimental design, with cluster random sampling. Collecting data using test techniques, questionnaires and observation. Data analysis is quantitative or statistical in nature, with the aim of testing the established hypotheses. The results of the research are based on the results of the questionnaire hypothesis test, to measure the happiness of learning conducted by researchers with a significant probability value of 2 thailood is 0.0000 less than 0.05 then H1 is accepted. There is an influence of the application of the use of virtual reality-based learning media on the learning happiness of students at Pagedongan 3 Public Middle School. Looking at the results of the post-test hypothesis testing, to measure critical thinking skills performed by researchers with a significant probability value of 2 thailood is 0.0000 less than 0.05. It can be concluded that H1 is accepted, so it can be concluded that there is an effect of applying the use of virtual reality-based learning media to the critical thinking skills of students in grade 7 at SMP Negeri 3 Pagedongan.